Integration of Islam in the Adat Basandi Syarak, Syarak Basandi Kitabullah in Minangkabau Society: Integrasi Agama Islam dalam Adat Basandi Syarak, Syarak Basandi Kitabullah di Masyarakat Minangkabau - Mariana, Mela; Sibawaihi; Nur Anna, Dian (The Department of Islamic History and Culture in cooperation with the Center for Islamic History and Culture in Aceh and Malay World Studies (PUSAKA), Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia, 2024)
Islam has undergone a long process of regeneration in Minangkabau, the integration between customs and Islam in Minangkabau is reflected in their philosophy of life,